Screen media and academic performance in the seventh graders - Ratu Meulya Rezeki; Soedjatmiko Soedjatmiko; Abdul Latief (Indonesian Pediatric Society, 2014)
Background Excessive screen media exposures have manynegative impacts on children, including academic performance.Studies on the impacts of screen media on academic performancehave been limited, especially in Indonesia.Objective To assess screen media use and academic performanceof7th graders in a junior high school, and to evaluate other factorspotentially affecting student academic performance.Methods This was a cross-sectional study using surveys,questionnaires, and 12-day logbooks, conducted from May toJuly 2012. Students were 129 students in the 7,h grade of JuniorHigh Sch ool 115 in Jakarta and selected by consecutive sampling.Chi square test and multivariate analyses with logistic regressioncalculations were used for statistical analysis.Results The prevalences of students using screen media for > 2hours per day were 39.5% on weekdays and 64.3% on weekends.The prevalence of students using screen media that was notappropriate for their age was 69% on weekdays and 63.6% onweekends. Screen media content on weekdays and weekendshad no impact on academic performance (OR 0.56; 95%CI 0.26to 1.20; P=0.136 and OR 0.97; 95%CI 0.47 to 1.00; P=0.934,respectively) . In addition, the duration of screen media useon weekdays and weekends had no association with academicperformance (OR 0.60; 95%CI 0.30 to 1.23; P=0.161 andOR 0.90; 95%CI 0.44 to 1.86; P=0.782, respectively). Factorssignificantly associated with students' above average academicperformance were female gender (OR 3 .26; 95%CI 1.38 to7.74; P=0.007), superior intelligence quotient (IQ) comparedto average IQ (OR 4.63; 95%CI 1.66 to 12.9; P=0.003), highlysuperior IQ compared to average IQ (OR 5.45; 95%CI 1.51 to19.64; P=0.009), as well as achievement motivation and existenceof learning strategy, including intermediate vs. low motivation(OR 4.09; 95%CI 1.14 to 14.7 ; P=0.031), and high vs . lowmotivation (OR61.1; 95%CI 7.42 to 502.95; P<0.001); lack ofemotional and behavioral problems (OR 0.45; 95%CI 0.37-0.54;P= 0.01); and democratic parenting style (OR 0.45; 95%CI 0.37to 0.55; P=0.022).Conclusion There is no association between screen media useand academic performance in junior high school students. Factorssignificantly associated with above average academic performanceare female gender, superior and very superior IQ score, middleand high achievement motivation and learning strategy, lack ofemotional and behavioral problems, and democratic parentingstyle.